Big data, cloud and applications : third International Conference, BDCA 2018, Kenitra, Morocco, April 4-5, 2018, Revised selected papers /: third International Conference, BDCA 2018, Kenitra, Morocco, April 4-5, 2018, Revised selected papers. (2018) - Unknown
No abstract available